HRCT Chest Evaluation of COVID-19 Patients: Experience in Combined Military Hospital Dhaka, Bangladesh - Alam, Syed Zoherul; Muid, SMA Al; Akhter, Afroza; Rahman, AKM Sharifur; Emran, Md Al; Mostakim, Md Tarif Al (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Background: HRCT Chest is an important tool in both diagnosis and management of COVID-19 patient, as well as it is an important complement to the reverse-transcription polymerase chain reaction (RT-PCR) tests. Purpose: The purpose of this study is to assess different patterns of manifestation in HRCT chest in COVID-19 infection & to grade the severity by observing a sample of 128 after the symptoms began. Method: From 11 April 2020 to 27 May 2020, 128 patients who were admitted in Combined Military Hospital Dhaka and underwent both HRCT chest and RT-PCR for COVID- 19 were included. Distribution and patterns of pulmonary lesions like ground glass opacity (GGO), consolidation, reverse halo sign, crazy paving, thickened vascular marking, lymphadenopathy and pleural effusion were evaluated. Result: Total 128 patients diagnosed (RT-PCR Positive) with COVID-19 were included. Among them, 112(87.5%) patients had fever, and 58(45.31%) patients had fatigability. The most frequent CT abnormality was ground glass opacity in 123(96.09%) cases. Amongst them 81(63.28%) cases had GGO plus consolidation and ground glass opacity alone were 42(32.81%) cases. Crazy-paving pattern was in 65(50.78%) cases. Most patients had multiple lesions and involved all the 5 lobes in 96(75.00%) cases. The lesions were mostly peripheral (123,96.09%) and posterior (103,80.47%) and in 65(50.78%) cases the distribution were diffuse but predominantly peripheral. Most commonly involved lobe is right lower lobe (120,93.75%) and left lower lobe(117,91.41%). Conclusion: HRCT chest can play an important role in the early diagnosis and prompt management of this global health emergency. J Bangladesh Coll Phys Surg 2020; 38(0): 21-28